2012
DOI: 10.1007/s11998-012-9396-8
|View full text |Cite
|
Sign up to set email alerts
|

Preferred partitioning: the influence of coalescents on the build-up of mechanical properties in acrylic core–shell particles (I)

Abstract: The partitioning of three coalescents of different polarity in different phases of multiphase acrylic particles was studied to provide a rationale for obtaining the desired performance of binders for wood coatings in terms of the ideal balance between hardness development, blocking resistance, and blushing resistance. Minimum film formation temperature-and aqueous differential scanning calorimetry-measurements on the hard phase polymer by itself showed the different extents to which both hydroplasticization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the first few days, the more hydrophilic BG apparently increased the water sensitivity of the film and facilitated ion diffusion from the test electrolyte; this resulted in higher values of σ c d c . According to past studies, better mechanical properties were obtained with more hydrophilic coalescing aids, whereas better early water resistance was obtained with more hydrophobic coalescing aids . The differences in the mechanical properties and Warburg diffusion could be explained by the partitioning of the coalescing aids during film formation.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In the first few days, the more hydrophilic BG apparently increased the water sensitivity of the film and facilitated ion diffusion from the test electrolyte; this resulted in higher values of σ c d c . According to past studies, better mechanical properties were obtained with more hydrophilic coalescing aids, whereas better early water resistance was obtained with more hydrophobic coalescing aids . The differences in the mechanical properties and Warburg diffusion could be explained by the partitioning of the coalescing aids during film formation.…”
Section: Resultsmentioning
confidence: 93%
“…Formulations with BG gave harder films and also a faster hardness buildup than PnB, even though the latter had a 20% higher evaporation rate. This might have been due to differences in the hydrophilicity and partitioning during drying, and indeed, other researchers have also found that the addition of hydrophilic coalescing aids to waterborne coatings leads to harder films than the addition of hydrophobic coalescing aids …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations